Use of Data Warehouse and Data Mining for Academic Data : A Case Study at a National University - Primasatria Edastama; Amitkumar Dudhat; Giandari Maulani (International Institute for Advanced Science & Technology (IIAST), 2021)
If an organisation has full, rapid, exact, and accurate information, it may perform better in terms of evaluation, planning, and decision-making. The essential information can be derived from operational data maintained in an integrated database by a university that already has an information system. This research looks at how to collect operational data into a data warehouse and then apply data mining techniques to analyse the data. This study yielded a comprehensive data warehouse with a web-based information reporting application. Furthermore, data mining techniques are used to analyse the data warehouse that has been created. The result of the application of data mining is the generation of characteristic patterns of students who take certain specialization programs.